(untitled) (Journal of Forest and Livelihood, 2024)
This guidebook has been published at a time when there is a widespread recognition in Nepal that community forests are not being actively managed to realize their full potential. Whilst there are both institutional and technical solutions to this problem, the guidebook has clearly spelled out its position in addressing the technical issues of forest management in a way field workers can really understand and articulate while working with forest user groups.